JURNAL AKUNTANSI MULTIPARADIGMA : Partisipasi Anggaran dan Kepuasan Kerja Manajemen Perguruan Tinggi Muhammadiyah se-Indonesia - Helmy Adam (Fak. Ekonomi dan Bisnis Universitas Brawijaya, 2010)
This research is aimed to find the causes of the inconsistencies in several research findings (Brownell 1981, 1982a; Frucot & Shearon 1991, Indriantoro 1995). Lucket & Eggleton’s finding (1991) of the role of locus of indicates that task uncertainty could determine the effect of locus of control as a moderating variable. This research involves 88 Dean/Financial Dean Assistants of Muhammadiyah Higher Education in Indonesia. Using 3-way interaction, it is shown that task uncertainty has significant effect on the locus of control’s moderating role. In higher task uncertainty conditions, managers who have internal locus of control will be more satisfied as higher participation occurs, while managers who have external locus of control, will be more dissatisfied when higher participation occurs. In contrast, in lower task uncertainty, locus of control does not indicate moderating roles, because both internal and external locus of controls has the same positive effect on responding the budgetary increasing participation.